Aerobic C−H Hydroxylation by Copper Imine Complexes: The Clip‐and‐Cleave Concept – Versatility and Limits. Issue 20 (2nd May 2021) - Specht, Pascal; Petrillo, Alexander; Becker, Jonathan; Schindler, Siegfried
Abstract: The intramolecular ligand hydroxylation of a series of copper(I) imine complexes during their reaction with dioxygen had been systematically studied. The so‐called clip‐and‐cleave concept offers a facile way to oxygenate aldehydes or ketones. A copper(I) complex for example, with an imine ligand derived from an ethylenediamine derivative and cyclohexanone was oxidized. Decomposing the complex after the reaction with hydrochloric acid showed a 50 % conversion of the cyclohexanone to 2‐hydroxycylohexanone. Depending on the ligand system, three different reaction pathways have been identified that can cause hydroxylation reactions. While the radical based mechanisms are more difficult to identify, the reactions that go through a copper bis( μ ‐oxido) complex as active species can be analyzed by low temperature stopped‐flow techniques. In an ideal case the formation and decomposition of this reactive intermediate can be spectroscopically observed. It was shown that this depends strongly on the ligand system: steric effects, chelate ring size and coordination number play an important role for the mechanism and the outcome of the reaction. Abstract : Copper(I) complexes with various bidentate imine ligands were reacted with dioxygen, which caused selective intramolecular hydroxylation reactions. In some cases, the copper bis( μ ‐oxido) complexes could be observed as intermediates by UV‐vis spectroscopy and kinetic investigations were carried out.